The influence of technological changes in energy efficiency on the infrastructure deterioration in the energy sector. (November 2021) - Shabalov, M.Yu.; Zhukovskiy, Yu.L.; Buldysko, A.D.; Gil, B.; Starshaia, V.V.
Abstract: The energy and its entire related infrastructure are the main drivers for a economic development and for ensuring a good level of employment. As part of a global study about international energy sector, we evaluate here the impact of technological changes on the state of the energy infrastructure. This study includes a detailed analysis of the global challenges facing the energy industry. We propose scenarios for the development of a modernized energy infrastructure with an assessment of the entire energy system. Our evaluation indicators are chosen in terms of the reliability of the energy infrastructure, of its quality, of the accidents that may happen and of the consequent environmental risks. This study is particularly adapted for forecasting the necessary measures (of technical nature, of governance kind) that have to be implemented to reduce the acceleration of the infrastructure deterioration rate. Our results reveal that the use of digital and information technologies has many positive impacts on the development and on the control of an efficient consumption of energy. In addition, our predictions, due to the further modernization of the energy sector, can contribute and help in the creation of preconditions that will be highly stimulating and profitable to the growth of investments in the energy infrastructure. Highlights: Global challenges affect on the state of infrastructure in the energy complex. The transformation of energy motivate the transition towards a low-carbon economy. Unrealized potential of energy saving exceeds 1/3 of the total energy consumption. Digital technologies improve the efficiency of functioning of energy infrastructure. Significant cost reduction are achieved by the emergence of a digital platform.